Writing revolution : Hispanic anarchism in the United States - Castaneda, Christopher James, 1959-; Feu López, M. Montserrat (Urbana : University of Illinois Press, 2019)
"Writing Revolution examines the international movement of Spanish-speaking anarchists who sought social and economic freedom in the United States. Scholars from Latin America, Spain, and the United States will trace the nineteenth-century origins of Spanish-language anarchism and explore the manner in which its ideas and practices crossed borders in the Americas and deeply influenced the development of U.S. Spanish-speaking culture and society from the nineteenth through the twentieth century. This is a book that not only explores the evolution and development of anarchist thought and action, it examines how people widely dispersed over time but who had a shared language and perspective on authoritarian regimes found solidarity through communication and work. Transnational Libertad proposes a global approach to U.S. Hispanic anarchist history, culture, and legacy by examining transnational channels and networks, particularly the anarchist press"--
Introduction: Hispanic anarchist print culture : writing from below -- Spanish republicanism and the press : the political socialization of anarchists in the United States (1880s-1910s) / Sergio Sánchez Collantes -- Globetrotters and rebels : correspondents of the Spanish-language anarchist press, 1886-1918 / Alejandro de la Torre -- Anarchism and the end of empire : José Cayetano Campos, labor, and Cuba Libre / Christopher J. Castañeda -- Red Florida in the Caribbean red : Hispanic anarchist transnational networks and radical politics, 1880s-1920s / Kirwin R. Shaffer -- Spanish-speaking anarchists in the United States : the newspaper Cultura Obrera and its transnational networks (1911-1927) / Susana Sueiro Seoane -- Spanish firemen and maritime syndicalism, 1902-1940 / Jon Bekken and Mario Martin Revellado -- Moving west : Jaime Vidal, anarchy, and the Mexican Revolution, 1904-1918 / Christopher J. Castañeda -- Caritina M. Piña and anarcho-syndicalism : labor activism in the greater Mexican borderlands, 1910-1930 / Sonia Hernández -- Traces of the Revista Única : appearances and disappearances of anarchism in Steubenville, 1909-1973 / Jesse Cohn -- The anarchist imaginary : Max Nettlau and Latin America, 1890-1934 / Jorell A. Meléndez-Badillo -- Reflections of the United States : through the pages of La Revista Blanca, 1923-1936 / María José Domínguez and Antonio Herrería Fernández -- Transnational anarchist culture in the interwar period : the magazine Estudios (1928-1937) / Javier Navarro -- Keepsakes of the revolution : transnational networks and the U.S. circulation of anarchist propaganda during the Spanish civil war / Michel Otayek -- España Libre, 1939-1977 : anarchist literature and antifascism in the United States / Montse Feu -- Federico Arcos (1920-2015) : an Iberian anarchist exile / David Watson.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on June 09, 2020).
JSTOR
Keywords: Anarchism -- United States -- History; Press, Anarchist -- United States -- History; Anarchists -- United States -- History; Hispanic Americans -- Politics and government; Hispanic American literature (Spanish) -- History and criticism; Anarchisme -- États-Unis -- Histoire; Presse anarchiste -- États-Unis -- Histoire; Anarchistes -- États-Unis -- Histoire; Littérature américaine (espagnole) -- Histoire et critique; SOCIAL SCIENCE -- General; Anarchism; Anarchists; Hispanic American literature (Spanish); Hispanic Americans -- Politics and government; Press, Anarchist; United States; Criticism, interpretation, etc; History